Identification of Hybrid Specimens of Rock Lizards Darevskia armeniaca × Darevskia valentini Based on Microsatellite Genotyping - Girnyk, A. E.; Vergun, A. A.; Ryskov, A. P. (Russian journal of genetics, 2023)
The paper presents the results of the microsatellite genotyping of hybrid lizards D. armeniaca × D. valentini from sympatric populations of Armenia. Triploid individuals are identified based on the totality of the Du281 and Du47G loci and their origin is determined. It is shown that the hybrids contain both alleles of the maternal parthenospecies D. armeniaca and alleles of the paternal species D. valentini .